Santris’ Attitudes Towards English in an Indonesian Islamic Boarding School - Saputra, Yuyus; Narulita Dewi, Nita Sari; Yusril Muharam, Muhammad (JALL (Journal of Applied Linguistics and Literacy), 2025)
This research aims to identify the factors that negatively affect santri's attitudes toward learning English in an Indonesian Islamic boarding school. Pre-observation revealed that approximately 29% of students exhibited behaviors such as lack of focus, motivation, and interest, often engaging in disruptive actions like joking around, sleeping in class, and neglecting their studies. To explore these factors, a descriptive case study was conducted, involving semi-structured interviews with three 11th-grade students. The findings reveal three primary themes: lack of exposure to English, language anxiety, and lack of motivation. Insufficient exposure to English hindered students’ proficiency, particularly in listening, reading, and pronunciation. Anxiety about making mistakes created emotional barriers, preventing students from engaging in English-speaking activities. Additionally, low motivation, often exacerbated by an uninspiring classroom environment and absence of peers, contributed to disengagement and negative attitudes. These insights emphasize the importance of addressing cognitive, affective, and behavioral factors to promote positive language attitudes and enhance language acquisition.